Breast lobular carcinoma metastatic to the cervix: case report - Wolff Barretto, Julia; Thereza Burko Rocha, Maria; Mazorra Coelho Vieira, Miguel; Ossamu Ioshii, Sérgio; Costa Linhares, Júlia (Mastology, 2025)
Breast cancer is the most common cancer among women, with 5 to 15% of these cases classified as invasive lobular carcinoma (ILC). Metastases can occur at any stage of the disease, with the most common sites being bones, lungs, lymph nodes, liver, and brain. However, extragenital metastasis to the uterus is rare. This study describes a case of a 52-year-old woman with breast pain for over a month. Mammography indicated a suspicious nodule (BIRADS 5). Physical examination revealed a breast nodule, peau d’orange skin, and axillary mass. Core biopsy diagnosed invasive lobular carcinoma. Tomographies suggested bone metastases. Additionally, she presented with abnormal uterine bleeding, and ultrasonography showed a suspicious uterine nodule, confirmed as a metastasis of ILC by immunohistochemical analysis. She had been treated with anastrozole since November 2023, with symptom reduction and clinical follow-up. It is known that ILC is the breast cancer most likely to metastasize to the genital tract. Previous reports mention difficulties in differentiation through imaging exams, with definitive differentiation achieved by biopsy of the cervix and/or later by surgery for tumor excision, with histopathological analysis and immunohistochemical profiling. There is limited scientific data on treatment options and prognosis in these cases. A study of approximately 1,650 patients with metastatic lobular carcinoma showed an overall survival of about 34 months. Thus, it is concluded that metastasis of invasive lobular carcinoma to the cervix is a rare entity, and this study aimed to contribute to the understanding of this condition and increase scientific evidence on the topic.